Water Resources Change in Central-Western Argentina Under the Paris Agreement Warming Targets - Rivera, Juan A.; Naranjo Tamayo, Elizabeth; Viale, Maximiliano (Frontiers in Climate, 2020)
This study documents the projected changes in several components (precipitation, runoff, snow cover and depth, soil moisture) of the hydrological cycle in Central-Western Argentina (CWA) based on the simulations from the IPSL-CM6A-LR model for the warming levels proposed in the Paris Agreement. These warming levels represent the future increase in mean annual temperature of 1.5 and 2°C compared to pre-industrial conditions. A novel regional approach, that uses a set of low-emissions shared socioeconomic pathways (SSP) compatible with the Paris Agreement goals, has been applied here for the evaluation of the potential impacts of temperature increase in both the mountainous areas of the Andes and the lowlands on the eastern portion of CWA. Our results show that the timing of reaching the 1.5°C warming level would be between 2032 and 2036 in the CWA lowlands east of the Andes, while this warming level in the Andes mountains of CWA would be 10–15 years earlier as result of the stronger warming with elevation. The higher 2°C warming level would be reached before 2050 in the Andes mountains. Even using the more aggressive mitigation pathways available in the scientific literature (SSP1-1.9 and SSP1-2.6), the IPSL-CM6A-LR model ensemble shows a robust drying signal in the wintertime precipitation over the Andes mountains, which is a concerning result because it implies a reduction of the already scarce water resources draining to the adjacent semi-arid foothills. Our results also show that this drying should be linked to the poleward expansion of the Hadley Circulation. In the lowlands farther east from the Andes, the summertime monsoonal precipitation provides the water resources that are projected to increase under the selected emissions pathways. The expected changes in the analyzed components of the hydrological cycle would be strengthened under the 2°C warming level, particularly the decline of snow amount and surface runoff in the Andes. The results of this study provide insights into the expected impacts of the 1.5 and 2°C warming levels in the CWA regional water resources, which may set the stage for the new discussions of possible options to mitigate them at country and regional levels.